(untitled) (Scientific Journal of Research Studies in Future Human Sciences, 2025)
Early Islamic historiography was the product of complex interactions between historians and political power structures. Islamic caliphates influenced historians' intellectual frameworks through various mechanisms such as financial support, intellectual restrictions, and discourse formation. This study aims to systematically review the mechanisms of how Islamic caliphates' politics influenced historians' content tendencies in early Islamic historical texts. By searching international databases (PubMed, Scopus, Web of Science, Google Scholar) and domestic databases (SID, Elmnet, Magiran, Noormags, Irandoc), 600 articles were identified. After applying inclusion criteria (relevance to the topic, clear methodology, analytical-critical approach, publication in credible sources, access to full text) and exclusion criteria (focus on periods other than early Islamic centuries, lack of power-knowledge relationship analysis, unclear methodology, publication in non-credible sources, repetitive content), 12 studies were selected for final analysis. The findings revealed that political-ideological developments in the caliphate structure led to the formation of different historical discourses. The transition from the Umayyad to the Abbasid caliphate created a fundamental shift in historiographical approaches, and the "secular tradition" of historiography was mainly formed by pro-Umayyad writers. Historians' positions within power relations had a decisive impact on the content of historical narratives, with independent historians presenting different narratives from court-affiliated historians. Additionally, the multiplicity of power centers in the Islamic world led to diverse historical discourses, and identity factors alongside political factors played a role in shaping historical narratives.